3D printing of UAV (II) - Lim, Chin Mian (2018)
Unmanned aerial vehicle (UAV) has evolved extensively in terms of design and the capability to perform different mission types since World War II. There were many innovations to cut down weight of UAV, to cut down time in fabrication and to strengthen the UAV to keep up with the changes. However, they were largely limited by the conventional manufacturing methods of UAV. Additive manufacturing (AM) offers an alternative to convention manufacturing which can remove those limitations. Many impressive UAVs have been fabricated using different AM technologies and achieved amazing time and weight savings. Nevertheless, additive manufacturing of UAV still requires much more streamline and research in terms of design optimization and structural integrity. Finite element (FE) analysis can be adopted in early design phase to reduce the trial-and-error and to optimize the design based on the load profile. In order to produce accurate FE analysis, the mechanical properties of the AM material are significantly necessary. Hence, this project aimed to investigate the orthotropic properties of the Acrylonitrile Styrene Acrylate (ASA), fabricated by fused deposition modelling (FDM). Results showed that raster and build orientation had noticeable effect on the Young’s modulus, yield strength, ultimate tensile strength but not on Poisson’s ratio. Mechanical properties of ASA were given to the FE team and allowed accurate and successful loading simulation during the initial design phase which prevented unnecessary reiteration of designs. Valuable information also helped in determining the optimized printing orientations and raster directions for additive manufacturing of UAV.